Modalities of extensor tendon repair related to etiological factors and associated injuries - Sanela Salihagić; Zlatan Zvizdić; Dženana Hrustemović; Redžo Čaušević; Ahmad Hemaidi (Medicinski glasnik, 2020)
Aim: To evaluate modalities of extensor tendons repair of hand and forearm in specific anatomical zones with regard to etiological factors and presence of associated injuries of adjacent anatomical structures. Methods: This cross-sectional study included 279 patients referred for extensor tendon repair of hand and forearm in specific anatomical zones. Available treatment modalities were evaluated concerning etiological factors, anatomical zones, and associated injuries. Statistical significance was analysed in the occurrence of early and late postoperative complications according to anatomical zones. Results: Direct repair of extensor tendon lesions was found to be the most common modality of reconstruction, 230 (93.5%), of which blade injuries were predominant, 120 (48.7%). Direct tendon repair was mostly indicated in Zone VI and Zone III, in 55 (23.9%) and 42 (18.3%) patients, respectively. Statistically, a significant correlation was confirmed between treatment modalities, injuries in specific anatomical zones, and type of etiological factor (p<0.0001). Statistical correlation was confirmed between zones of injuries and the occurrence of early and late complications (p=0.002). Conclusion: Successful postoperative recovery was correlated with the recognition of functional failure in specific zones, assessment of potential associated injuries, and selection of the most optimal modality of reconstruction.
Keywords: associated injury; etiologic factors; extensor tendons; tendon repair